2018
DOI: 10.1002/hsr2.88
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management recommendations for sickle cell disease: A Ghanaian health professionals' perspective

Abstract: ObjectiveTo describe self‐management recommendations for sickle cell disease (SCD) care among health professionals who manage SCD in Ghana.MethodNine health care professionals (nurses, doctors, and physician assistants) who work in SCD were interviewed. The semistructured interviews were recorded, transcribed, and analysed using the qualitative content analysis method. Self‐management recommendations were conceptualised as preventive health, self‐monitoring, self‐diagnosis, self‐treatment, and self‐evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(85 reference statements)
2
2
0
Order By: Relevance
“…The findings among the children have not been previously described but could be influenced by what health professionals teach them as the findings parallel health professionals’ recommendations in our previous publication. 39 The findings among the adults are similar to findings among adults in the US study where the participants described “self-awareness” or “listening to and learning about the body” as the major strategies for self-monitoring. 32,33,40…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings among the children have not been previously described but could be influenced by what health professionals teach them as the findings parallel health professionals’ recommendations in our previous publication. 39 The findings among the adults are similar to findings among adults in the US study where the participants described “self-awareness” or “listening to and learning about the body” as the major strategies for self-monitoring. 32,33,40…”
Section: Discussionsupporting
confidence: 82%
“…The findings among the children have not been previously described but could be influenced by what health professionals teach them as the findings parallel health professionals' recommendations in our previous publication. 39 The findings among the adults are similar to findings among adults in the US study where the participants described "self-awareness" or "listening to and learning about the body" as the major strategies for self-monitoring. 32,33,40 The findings further revealed that whereas the parents consciously conducted the mentioned self-monitoring actions such as urine and eye colour checks, the adults selfmonitoring and diagnosis actions occurred as automatic unconscious responses to changes in health status.…”
Section: Discussionsupporting
confidence: 81%
“…Managing pain associated with diarrhea or sickle cell crises is important. [ 10 , 11 ] Appropriate pain medications and pain management strategies should be part of the treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…The life expectancy in SCD is generally decreased (possibly 20 -30 years) in comparison with undiseased persons, nonetheless, loans in treatment are extending survival. The consequences for utmost cases are protected and SC crises frequently need readmissions to the hospice [10].…”
Section: Introductionmentioning
confidence: 99%